2010
DOI: 10.5487/tr.2010.26.2.137
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide Transcriptional Response During the Development of Bleomycin-Induced Pulmonary Fibrosis in Sprague-Dawley Rats

Abstract: Pulmonary fibrosis is a common consequence of many lung diseases and a leading cause of morbidity and mortality. The molecular mechanisms underlying the development of pulmonary fibrosis remain poorly understood. One model used successfully to study pulmonary fibrosis over the past few decades is the bleomycin-induced pulmonary fibrosis model. We aimed to identify the genes associated with fibrogenesis using an Affymetrix GeneChip system in a bleomycin-induced rat model for pulmonary fibrosis. To confirm fibro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 40 publications
0
6
0
Order By: Relevance
“…Other, rarer fusions were also identified, including GAS7-MYH1 and ZCCHC8-RSRC2 , each of which were identified in 4 ILD samples and have been reported previously in cancer samples ( GAS7-MYH1 in lung and stomach adenocarcinoma, and ZCCHC8-RSRC2 in multiple cancers) [ 52 ]. Interestingly, expression of MYH1 has previously been found to be upregulated in the bleomycin mouse model of idiopathic pulmonary fibrosis (IPF) [ 53 ]. Overall, although fusions are rare in ILD, these data indicate the potential for revealing molecular information that may be relevant to disease manifestation.…”
Section: Resultsmentioning
confidence: 99%
“…Other, rarer fusions were also identified, including GAS7-MYH1 and ZCCHC8-RSRC2 , each of which were identified in 4 ILD samples and have been reported previously in cancer samples ( GAS7-MYH1 in lung and stomach adenocarcinoma, and ZCCHC8-RSRC2 in multiple cancers) [ 52 ]. Interestingly, expression of MYH1 has previously been found to be upregulated in the bleomycin mouse model of idiopathic pulmonary fibrosis (IPF) [ 53 ]. Overall, although fusions are rare in ILD, these data indicate the potential for revealing molecular information that may be relevant to disease manifestation.…”
Section: Resultsmentioning
confidence: 99%
“…The chronic bleomycin model of lung inflammation (producing lung inflammation that persists for more than 8 days) was initially optimised in house based on previously published procedures [26,27]. A single bleomycin dose of 2.8 mg/kg delivered via liquid intratracheal instillation (as previously described [11,17]) in a volume of 100 ul sterile saline was optimally found to produce significant lung inflammation over 8 days without adversely impacting the health and general wellbeing of rats.…”
Section: Plasma Pharmacokinetics and Lung Clearance Of Ciprofloxacin mentioning
confidence: 99%
“…Further, with regard to the total cell count and differential inflammatory cell count in BALF, there was no significant difference among the groups before and after exposure. Previous studies have shown that when the lung is exposed to a toxic material, inflammations generally occur after 2 days and manifest after 7 days of exposure (Yang et al, 2008 ; Park et al, 2010) .…”
Section: Discussionmentioning
confidence: 99%